Primary sclerosing cholangitis - Milkiewicz, Piotr; Wunsch, Ewa (Recent results in cancer research, 2011)
Primary sclerosing cholangitis (PSC) is a chronic liver condition which may affect both intra and extrahepatic biliary tree. Etiology of PSC remains to be fully elucidated but genetic, autoimmune, inflammatory and possibly infective factors could all contribute to its development. More than two-thirds of patients are males and the most commonly associated condition is an inflammatory bowel disease which occurs in up to 70% of affected subjects. Endoscopic cholangiopancreatography (ERCP) and magnetic resonanse cholangiopancreatography (MRCP) remain a gold standard in the diagnosis of this condition. No curative treatment of PSC exists and a proportion of patients who develop liver failure or suffer from recurrent episodes of cholangitis requires liver transplantation. PSC is associated with increased risk of malignancies, in particular cholangiocarcinoma which may arise in 12% of patients. The main aim of this chapter is to review the current knowledge on pathogenesis and clinical aspects of PSC as well as its associated malignancies.